Thrombin‐generating potential, plasma clot formation, and clot lysis are impaired in patients with bleeding of unknown cause. (15th July 2019) - Hofer, Stefanie; Ay, Cihan; Rejtö, Judit; Wolberg, Alisa S.; Haslacher, Helmuth; Koder, Silvia; Pabinger, Ingrid; Gebhart, Johanna
Abstract: Background: In a large proportion of patients with a mild to moderate bleeding tendency no diagnosis can be established (bleeding of unknown cause, BUC). Objectives: To investigate possible dysfunctions in thrombin generation and plasma clot formation and lysis in patients with BUC from the Vienna Bleeding Biobank (VIBB). Patients and Methods: Thrombin generation and plasma clot properties of 382 BUC patients were compared to those of 100 healthy controls and 16 patients with factor VIII (FVIII) activity ≤50%. Results: Thrombin generation was significantly impaired in BUC patients compared to healthy controls, exhibiting a prolonged lag time and time to peak and decreased maximum thrombin generation, velocity index, and area under the curve (AUC). The assessment of clot formation and lysis in BUC patients revealed a lower clot formation rate (Vmax), resulting in a longer TTP, increased absorbance (ΔAbs), and a shorter clot lysis time (CLT) than in healthy controls. Comparing patients with FVIII activity ≤ 50% to those with BUC, parameters of thrombin generation and clot formation and lysis were either stronger or comparably impaired. Bleeding severity did not correlate with parameters of thrombin generation, clot formation, or clot lysis. Conclusion: Patients with BUC have an impaired hemostatic capacity reflected by a lower thrombin‐generation potential, a lower clot formation rate, increased clot turbidity, and shorter clot lysis time, which might contribute to their increased bleeding tendency. Assays monitoring these parameters can alert physicians of hemostatic impairment and should be considered in situations where traditional hemostatic lab tests fail to reveal the clinical bleeding tendency.